2020
DOI: 10.1155/2020/2863501
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Intravenous Injections of Valproic Acid‐Induced Mesenchymal Stem Cell from Human‐Induced Pluripotent Stem Cells Improved Cardiac Function in an Acute Myocardial Infarction Rat Model

Abstract: Mounting evidence indicates that the mesenchymal stem cell (MSC) injection is safe and efficacious for treating cardiomyopathy; however, there is limited information relating to multiple intravenous injections of human-induced pluripotent stem cell-derived mesenchymal stem cell (hiPSC-MSC) and long-term evaluation of the cardiac function. In the current study, MSC-like cells were derived from human-induced pluripotent stem cells through valproic acid (VPA) induction and continuous cell passages. The derived sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In our previous study, we reported that four rounds of IV infusions of 1x10 6 MSCs to AMI rats could improve cardiac function. The higher dosage of 2-3x10 6 cells caused severe dyspnoea in a number of the model rats and resulted in the death of 20-50% of the animals within a short time frame, which was potentially related to pulmonary embolism (44). In the present study, in order to avoid the potential risk of small blood vessel cell embolism, IP injections were used and cell dosage was increased to 1x10 7 cells, 10x as high as the previous IV injections in order to test the safety of high dosage IP injections.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we reported that four rounds of IV infusions of 1x10 6 MSCs to AMI rats could improve cardiac function. The higher dosage of 2-3x10 6 cells caused severe dyspnoea in a number of the model rats and resulted in the death of 20-50% of the animals within a short time frame, which was potentially related to pulmonary embolism (44). In the present study, in order to avoid the potential risk of small blood vessel cell embolism, IP injections were used and cell dosage was increased to 1x10 7 cells, 10x as high as the previous IV injections in order to test the safety of high dosage IP injections.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple injections of stem cells are clinically challenging in terms of efficacy, safety, and cost. Nonetheless, prior research using animal models in various diseases and settings such as diabetes mellitus, 5 spinal cord injury, 6 ischemic cardiomyopathy, 7 and vascularized composite allotransplantation 8 suggested the potential for the clinical application of multiple injections of mesenchymal stem cells (MSCs). However, the efficacy of multiple intravenous injections of adipose-derived stromal cells for fat grafting has not yet been studied.…”
mentioning
confidence: 99%